Estimation of Fishing Ground on Sea Surface Temperature Distribution and Cholophyll-a in The Waters of the Tolo Bay - Kamsina, Kamsina; Masyahoro, Masyahoro; Laapo, Alimudin (Mitra Sains, 2021)
One of the major problem for fishermen of Tolo Bay water in optimizing the utilization of the fish resources is the difficulty in determining potential fishing grounds. The fishing area is very much determined by the distribution of oceanographic parameters, in particular the distribution of sea surface temperature and chlorophyll-a concentration. The aim of the reaserch is to estimate the fishing ground using integrated sea surface temperature and chlorophyll-a distribution image data from Aqua-Modis Level 3 Satellite and Seades 7.2. The Reseacrh was conducted using GIS-based Remote Sensing Method and Field Survey through in situ measurement (ground check) as validation data. Satellite image data in the form of sea surface temperature distribution and cholorophyll-a were analyzed using ArgGIS 10.2 software. Recorder sea surface temperature and cholorophyll-a image data were obtained from National Institute Of Aeronautics and Space (LAPAN) as well as data from observations at 10 station. The results of research on estimating potential fishing ground in the water of Tolo Bay based on the distribution of sea surface temperature and cholorophyll-a concertractions are integrated in the fishing ground zoning in July with nine coordinate points.